1999
DOI: 10.1063/1.478624
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the electronic spectrum of magnesium-porphyrin

Abstract: Multiconfigurational self-consistent field ͑SCF͒ and second order perturbation methods have been used to study the electronic spectrum of magnesium-porphyrin ͑MgP͒. An extended ANO-type basis set including polarization functions on all heavy atoms has been used. Four allowed singlet states of E 1u symmetry have been computed and in addition a number of forbidden transitions and a few triplet states. The results lead to a consistent interpretation of the electronic spectrum, where the Q band contains one transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 43 publications
5
56
0
1
Order By: Relevance
“…[89] Vertical excitation energies from different electronic-structure methods have also been compared for D 4h -symmetric metalloporphyrins in terms of the Gouterman model. [5] For this type of compound, it was concluded that TDDFT/SAOP, TDDFT/BP86, and MRMP are in better agreement with experimental data than CASPT2(14/16) [90] and TDDFT/B3LYP calculations: CASPT2 underestimates the B band of Mg porphin and B3LYP overestimates the B band of Zn porphin.…”
Section: Theoretical Methodsmentioning
confidence: 60%
“…[89] Vertical excitation energies from different electronic-structure methods have also been compared for D 4h -symmetric metalloporphyrins in terms of the Gouterman model. [5] For this type of compound, it was concluded that TDDFT/SAOP, TDDFT/BP86, and MRMP are in better agreement with experimental data than CASPT2(14/16) [90] and TDDFT/B3LYP calculations: CASPT2 underestimates the B band of Mg porphin and B3LYP overestimates the B band of Zn porphin.…”
Section: Theoretical Methodsmentioning
confidence: 60%
“…All IVO-CASCI and CASSCF calculations are performed using a CAS (16/12), where the first entry of CAS (m/n) denotes the number of active electrons and the second entry indicates the number of active orbitals. The active orbitals used in the IVO-CASCI and CASSCF calculations comprise eight bonding valence π -orbitals (3b 1u , 2b 2g , 2b 3g , and 1a u ) and four anti-bonding valence π * -orbitals (1b 1u ,1b 2g ,1b 3g , and 1a u ), thus having the same designations as that employed by Rubio et al 25 in their (multiconfigurational second-order perturbation theory (CASPT2) based on a CASSCF reference wave function) studies for MgP. The choice of a chemically appropriate and optimal CAS is important for an accurate determination of the minimum energy structures and energetics of molecules.…”
Section: Resultsmentioning
confidence: 98%
“…65 This transition is buried under the B band in MgPz, while it results in a distinguishable shoulder, sh 1 , of the B band in NiPz.…”
Section: Excited States and Optical Spectramentioning
confidence: 99%